2022
DOI: 10.1111/pai.13757
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and childhood asthma: Analysis of a pediatric referral hospital

Abstract: To the Editor, Spain has been one of the epicenters of the SARS-CoV-2 pandemic.Children (0-14 years-old) account at least for 10.5% of all cases and usually develop mild severity of coronavirus disease 20191 Clinical observations point out allergy and/or asthma are not risky conditions in pediatric patients with COVID-19, 2 and hypothetically, allergic sensitization could be inversely related to the expression of COVID-19. 3 However, little is known about the effect of SARS-CoV-2 infection in allergic and/or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Childhood asthma was considered a major protective factor against severe COVID-19 in our study, and there have been many reports on childhood asthma and severe COVID-19. In Spain, children were thought to usually develop mild COVID-19 40 . Clinical observations indicated that allergies or asthma were not hazardous conditions in pediatric patients with COVID-19 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood asthma was considered a major protective factor against severe COVID-19 in our study, and there have been many reports on childhood asthma and severe COVID-19. In Spain, children were thought to usually develop mild COVID-19 40 . Clinical observations indicated that allergies or asthma were not hazardous conditions in pediatric patients with COVID-19 41 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of COVID-19 patients in children and young people found that patients with asthma were less likely to be admitted to critical care and less likely to die 42 . Data from a pediatric referral hospital indicated that the prevalence of asthma in pediatric patients with COVID-19 was low, with varied clinical manifestations and laboratory findings 40 . New confirmed cases of childhood asthma in Japan dropped significantly after the COVID-19 pandemic began, and 15 months later they have not recovered 43 .…”
Section: Discussionmentioning
confidence: 99%